Estudo da atividade tipo-ansiolítica das folhas de Pimenta pseudocaryophyllus (Gomes) L.R. Landrum - Myrtaceae - Fajemiroye, James Oluwagbamigbe (2012)
Pimenta pseudocaryophyllus, popularly known as Craveiro, is the only species in this genus native to the cerrado of Brazil. Ethnopharmacological studies revealed medicinal use of P. pseudocaryophyllus extracts in treating menstrual and digestive problems as well as emotional tension in the form of soothing tea among other therapeutic applications in Brazilian folk medicine. Its popular use is of great interest given the alarming increase in neural diseases and search for innovative herbal therapy. For the purpose of this study, the ethanolic leaf extract of Pimenta pseudocaryophyllus (EEPp) was obtained by soaking the dried leaf powder in ethanol (95%, 1:5). The fractions of hexane (FH), dichloromethane (DF), ethyl acetate (EAF) and aqueous (AF) were subsequently prepared through EEPp fractionation with solvents of different polarities. Mice weighing between 25 - 35g were treated acutely (sc / p.o / i.p) for the general test of pharmacological activity while oral administration was later explored for most of the central action screening considering lack of any sign of neurotoxicity even at the highest dose (2 g/Kg). Sleep induced by barbiturates was potentiated by the ethanolic leaf extract (1 g/Kg) through prolongation of sleeping time (duration) and reduction in time taken for the loss of righting reflex (latency). Identification of the active fraction of this extract was performed using behavioural models, such as sleep induced, open field, light / dark box test (LDB) and elevated plus maze (EPM). In this manner, only EAF (0.42 g/Kg) and HF treatments did not increase sleep duration and failed to demonstrate anxiolytic like effect. Meanwhile, treatment with DF (0.25 g/Kg) and AF (0.64 g/Kg) showed an increase in sleep duration and significant alterations of time and number of crossing at the centre of the open field. The AF demonstrated sedative effect in the LDB. Meanwhile, the DF (0.125, 0.25 or 0.5 g/Kg) showed anxiolytic like activity in both the LDB and EPM in a dose- dependent manner. These results suggested the presence of active principles of the P. pseudocaryophyllus that may be useful in developing a drug for the treatment of anxiety. It is worthy to state that no sign of neurotoxicity or motor incoordination was observed with DF treatment. In an attempt to elucidate the mechanism of action involved, pre-treatment with flumazenil (antagonist of benzodiazepine site of GABAA receptor) did not block anxiolytic-like effect of DF thereby excluding the participation of this site. However, this effect was reversed by pretreatment with NAN-190 (an antagonist of the 5-HT1A). This result suggests a possible involvement of the serotonergic system. In this case the results obtained on the neuropharmacological activity of dichloromethane fraction showed promising effect in anxiety model which require further extensive study to characterize neurobiological pathways involved for possible clinical application and better understanding of the pathophysiology of this neural disorder.